Hemostatic Effect of Ethanol Extract of Piper betle, Linn Leaves to Male Mice - Sadakata Sinulingga; Subandrate Subandrate; Bebbi Arisya Kesumaputri; Galuh Anggraini (Universitas Jenderal Soedirman, 2017)
Hemorrhage occurs in most of the dental care. Untreated hemorrhage could cause excessive blood loss, hypotension, and cyanosis. A Natural resource that reported has an hemostatic effect is ethanol extract of betel leaves (Piper betel, Linn).The aim of this study is to find the minimum concentration of ethanol extract of betel leaves which capable of shortening the bleeding time in mice. The experimental study used pretest-posttest with control group design was conducted on 35 mice that divided into 7 group which are negative control, positive control (feracrylum 1%), the ethanol extract of betel leaves 1%, 5%, 10%, 15%, and 20%. All mice were injected heparin intravenously. Miceâs tail was cut at diameter 3 mm and pretest bleeding time was counted. Miceâs tail was recut at diameter 4 mm, given treatment for 5 seconds and posttest bleeding time was counted. Results of paired t-test showed that reduction of bleeding time between pretest and posttest was significant (p<0,050). The enhancement of ethanol extract of betel leaves concentration leads to better hemostatic effect. Results of ANOVA test showed that comparison of posttest bleeding time among groups was significant (p<0,050). The minimum concentration of ethanol extract of betel leaves which capable of shortening the bleeding time in mice is 5%.